Challenges and Enablers of Deprescribing: A General Practitioner Perspective - Ailabouni, Nagham J. (PLoS One, 2016)
AIMS: Deprescribing is the process of reducing or discontinuing medicines that are unnecessary or deemed to be harmful. We aimed to investigate general practitioner (GP) perceived challenges to deprescribing in residential care and the possible enablers that support GPs to implement deprescribing. METHODS: A qualitative study was undertaken using semi-structured, face-to-face interviews from two cities in New Zealand and a purpose-developed pilot-tested interview schedule. Interviews were recorded with permission and transcribed verbatim. Transcripts were read and re-read and themes were identified with iterative building of a coding list until all data was accounted for. Interviews continued until saturation of ideas occurred. Analysis was carried out with the assistance of a Theoretical Domains Framework (TDF) and constant comparison techniques. Several themes were identified. Challenges and enablers of deprescribing were determined based on participants’ answers. RESULTS: Ten GPs agreed to participate. Four themes were identified to define the issues around prescribing for older people, from the GPs’ perspectives. Theme 1, the ‘recognition of the problem’, discusses the difficulties involved with prescribing for older people. Theme 2 outlines the identified behaviour change factors relevant to the problem. Deprescribing challenges were drawn from these factors and summarised in Theme 3 under three major headings; ‘prescribing factors’, ‘social influences’ and ‘policy and processes’. Deprescribing enablers, based on the opinions and professional experience of GPs, were retrieved and summarised in Theme 4. CONCLUSION: The process of deprescribing is laced with many challenges for GPs. The uncertainty of research evidence in older people and social factors such as specialists’ and nurses’ influences were among the major challenges identified. Deprescribing enablers encompassed support for GPs’ awareness and knowledge, improvement of communication between multiple prescribers, adequate reimbursement and pharmacists being involved in the multidisciplinary team.